2021
DOI: 10.18412/1816-0395-2021-2-60-65
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of the Impact of Meteorological Parameters on Man-Made Pollution by Carcinogenicly Dangerous Chemicals in the Voronezh Air Basin

Abstract: Based on the analysis of official statistics from the Voronezh Hydrometeorological Service, the patterns of the dynamics of pollutants (formaldehyde and soot) are investigated depending on the combination of various meteorological parameters — air temperature, wind speed, relative air humidity. A positive relationship has been established between the increase in atmospheric pollution with formaldehyde and air temperature. With increasing wind speed and relative humidity, the concentration of formaldehyde and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…The share of the contribution of each toxicant from the group of priority air pollutants to the increase in the assessment of environmental damage can be traced in Figure 2. Figure 2 clearly shows that 76% of the contribution to the reassessment of harm is allocated to suspended substances [14][15][16], and such natural pollutants as carbon monoxide, sulfur dioxide and nitrogen oxides make up 7.4 %, 3.3% and 2.3%, respectively, in the overall assessment of harm. In the event of unfavourable meteorological conditions, an additional coefficient of KNMU is introduced into the formula (1), according to which the influence of meteorological factors on the decrease in the assimilation capacity of atmospheric air is taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…The share of the contribution of each toxicant from the group of priority air pollutants to the increase in the assessment of environmental damage can be traced in Figure 2. Figure 2 clearly shows that 76% of the contribution to the reassessment of harm is allocated to suspended substances [14][15][16], and such natural pollutants as carbon monoxide, sulfur dioxide and nitrogen oxides make up 7.4 %, 3.3% and 2.3%, respectively, in the overall assessment of harm. In the event of unfavourable meteorological conditions, an additional coefficient of KNMU is introduced into the formula (1), according to which the influence of meteorological factors on the decrease in the assimilation capacity of atmospheric air is taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…В последние годы проблема формальдегидного загрязнения всё чаще обсуждается в работах отечественных и зарубежных авторов. Исследования, проведённые в городах Воронеже [1], Томске [2], Москве [3], Ижевске [4], Норильске, [5], Кирове и Ухте [6], а также в иностранных городах [7], показывают характерную картину повышенного содержания поллютанта как в примагистральных и промышленных зонах, так и в зонах жилой застройки, что является наиболее опасным фактором для здоровья населения, проживающего на территориях, This article discusses the issues of air pollution with formaldehyde and the impact of this pollutant on the health of the population of the city of Lipetsk. The study revealed patterns of increase in the concentration of formaldehyde in the warm season (May-September).…”
unclassified